Yttrium and Nickel Co-Doped BaZrO3 as a Proton-Conducting Electrolyte for Intermediate Temperature Solid Oxide Fuel Cells. (2nd June 2015) - P. Shafi, Shahid; Bi, Lei; Boulfrad, Samir; Traversa, Enrico
Abstract : High temperature proton conducting oxides, due to their lower activation energy for proton conduction, can achieve high conductivity at relatively low temperatures (500-700 °C). Though BaZr0.8 Y0.2 O3-δ (BZY) perovskite exhibits good chemical stability and high bulk conductivity, high grain boundary resistance decreases its total conductivity. This work focuses on substitution of Zr 4+ with Ni 2+ in the perovskite B-site in a targeted fashion in order to promote the sinterability of BZY. Powder X-ray diffraction analysis showed the formation of single phases for Ba0.8-x Y0.2 Nix O3-δ compositions up to x = 0.04. Scanning electron microscopy (SEM) image analysis demonstrated that densification is promoted by the increasing Ni-content, reaching a fully dense microstructure for Ba0.76 Y0.2 Ni0.04 O3-δ (BZYNi04). An anode supported single cell based on BZYNi04 electrolyte showed superior power performance, achieving 240 and 428 mW cm -2 at 600 and 700 °C, respectively.